Тұрмыс аясындағы абайсыз қылмыстардың жасалу механизмі - Уəлиева, Ж.Б. (ҚарМУ басп, 2010)
В статье рассматриваются вопросы механизма совершения неосторожных бытовых преступлений. Проводится сравнительный анализ определений различных авторов, на основе которого автор предлагает свои выводы по определению понятия механизма неосторожных преступлений. Раскры- ваются основные элементы механизма совершения неосторожных бытовых преступлений на основе практического материала. In presented clause questions of the mechanism of fulfilment of careless household crimes are considered. The comparative analysis of definitions of various authors and on the basis of the given analysis is spent, the author offers the conclusions by definition of concept of the mechanism of careless crimes. As on the basis of set of practical materials basic elements of the mechanism of fulfilment of careless household crimes reveal.